ANASLISIS PERSEPSI MAHASISWA TERHADAP PENGGUNAAN PAYLATER DAN DAMPAKNYA TERHADAP PERRILAKU KEUANGAN - Achmarul Fajar; Aditya Iskandar Syah; Rifki Riyadi; Saniman; Nurul Musthofa (Jurnal Riset Multidisiplin Edukasi, 2026)
This study, entitled "Analysis of Student Perceptions on the Use of Paylater and Its Impact on Financial Behavior," was written by Aditya Iskandar Syah, Rifki Riyadi, Saniman, and Nurul Musthofa from the Faculty of Economics and Business, Universitas Madura. This study aims to analyze student perceptions of the use of paylater services and their impact on financial behavior in the digital era. The research method used was a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The study sample consisted of 200 students who use paylater services such as Shopee Paylater, GoPayLater, Kredivo, and Akulaku, selected using a purposive sampling technique. The results show that students have a positive perception of paylater services because they are considered practical, easy to use, and offer easy payment options and various attractive promotions. However, the use of paylater also leads to increased consumer behavior, impulsive buying, and habitual behavior among students. Furthermore, low financial literacy and the influence of modern lifestyles also influence students' behavior in using paylater services. This study concludes that while using PayLater provides positive impacts in the form of transaction convenience and short-term financial assistance, it can also negatively impact financial management if used excessively. Therefore, improving financial literacy and self-control is necessary so that students can use PayLater services wisely and responsibly.